Political Technologies: The Interaction of Old and New. Issue 1 (29th March 2021) - Vinogradova, Svetlana; Melnik, Galina; Shaldenkova, Tatyana
Abstract: Political analysts believe that in the history of the development of society, we can observe two interrelated phenomena. The first is related to the introduction of new content in the old political forms, the second – with the filling of new forms of old content. From our point of view, the conclusion of political analysts may be used in the case of political technologies. Political technologies that use different types of effects on individuals and social groups are considered to be a relatively new phenomenon in the world of politics. In this article, we aim to clarify whether all the components of modern political technologies are fundamentally new.